Diagnosis dan Tata Laksana Frambusia - Saap, Evan Nugroho (PT Kalbe Farma Tbk., 2024)
Yaws is a chronic endemic treponematosis infection caused by the microaerophilic spirochete bacteria Treponema pallidum subspecies pertenue. The bacteria is spread by skin-to-skin contact in a warm and moist environment, especially among children. This disease is endemic in 15 countries, including Indonesia. The disease is classified by the World Health Organization (WHO) as neglected tropical diseases and targeted for eradication by 2030. Knowledge and skills of medical personnel for early diagnosis and providing appropriate treatment need to be improved to achieve the eradication target.